Arm spasticity after stroke: botulinum toxin therapy in combination with multimodal stimulation - V. N. Lutsik; E. V. Slyunkova; S. V. Kotov; V. K. Misikov; E. V. Biryukova (Неврология, нейропсихиатрия, психосоматика, 2020)
Post-stroke spasticity (PS) occurs in most patients with stroke and contributes to the development of pain syndrome and contractures, which substantially impairs the restoration of lost motor functions (MFs) and the quality of life of the patient.Objective: to evaluate the efficacy of a combination of botulinum toxin A (BTA) and multimodal stimulation in patients with arm PS.Patients and methods. The investigation enrolled 84 patients aged 18 to 85 years with PS, who had experienced ischemic stroke (IS) 1 month to 1 year before. In the study group (n=56), complex rehabilitation treatment was preceded by the use of BTA, while in the control group (n=28), multimodal rehabilitation therapy was performed without using BTA. Before and after treatment, neurological deficit was evaluated using the modified Ashworth scale (MAS), the Fugl—Meyer (FM) assessment scale, the British muscle strength grading scale, the Action Research Arm Test (ARAT), the Barthel index, and the modified Rankin scale.Results and discussion. According to MAS, there was a statistically significantly spasticity reduction after BTA use in the study group compared to the control one (median 1 [1; 2] and 2 [2; 3] scores, respectively; p=0.0003). According to the FM scale, an improvement in arm MFs was noted in the study group compared to the control one (median 29.5 [20; 42] and 21 [13.5; 31.5] scores, respectively; p=0.008) and according to the ARAT scale this was observed in the study and control groups (14.5 [7; 27] and 3 [0; 12] scores, respectively; p=0.0004).In patients with upper limb PS, the use of BTA before a rehabilitation cycle using multimodal stimulation was shown to be statistically significantly more effective than the similar neurorehabilitation cycles without prior BTA therapy. The findings can be used in the routine practice of a neurologist when planning rehabilitation for more effective and well-founded treatment in patients with arm PS.Conclusion. Incorporation of BTA into multimodal stimulation was ascertained to be effective in patients with PS.